Considerations for future disaster registries: Effectiveness of treatment referral outreach in addressing long-term unmet 9/11 disaster needs. Issue 3 (4th June 2018) - Petrsoric, Lysa; Miller-Archie, Sara A.; Welch, Alice; Cone, James; Farfel, Mark
Abstract : Purpose: The purpose of this paper is to evaluate the effectiveness of a targeted outreach program that referred World Trade Center Health Registry (Registry) enrollees, to specific post-disaster health care available through the World Trade Center Health Program (WTCHP) and evaluate differences in outreach effectiveness based on demographic and health characteristics. Design/methodology/approach: The Registry's Treatment Referral Program (TRP) targeted 22, 981 enrollees based on symptoms and conditions known to be related to 9/11, reported on a 2011-2012 follow-up survey. A call vendor was utilized for the initial outreach phone call. Enrollees who requested a WTCHP application had follow-up from TRP staff, which typically included 4-6 interactions per enrollee until outreach was completed. Findings: As of 12/31/2015, the vendor had reached 8, 778 (38 percent) of the targeted sample. TRP staff spoke to 6, 016 (68 percent) enrollees reached by the vendor, 5, 554 (92 percent) of whom requested a WTCHP application, and 2, 425 (43 percent) reported having submitted the WTCHP application. Application requests and submissions differed by survivor or responder status, race, income and health symptoms. Originality/value: Registries created for surveillance and research among disaster-exposed populations provide a unique and effective outreach approach. A dedicated treatment referral unit within a disaster registry is an effective means for conducting post-disaster outreach to a large, diverse sample of exposed individuals.